ROLE OF NITRIC OXIDE IN THE EFFECT OF NEBIVOLOL ON ISOLATED TRACHEAL MUSCLE OF GUINEA PIG - Shaukat, Asma; Abrar, Naila; Naureen, Ayesha; Nawaz, Muhammad (Journal of Ayub Medical College Abbottabad, 2013)
Background: The use of beta blockers is limited by their ability to produce bronchospasm in asthmatics. Third generation Î²-blockers like Nebivolol may show better tolerability because they may augment the release of nitric oxide (NO) from endothelial cells. However the involvement of NO in the respiratory effect of Nebivolol remains controversial. The present study, carried out on isolated tracheal muscle strips of guinea pigs, was designed to explore this controversy. Method: Varying concentration of histamine ranging from 10'‘7 M to 10'‘3 M were used to plot a concentration response curve on the isolated tracheal muscle strips of guinea pig and was used as a control. The same concentration response curve was plotted in presence of a fixed concentration of Nebivolol 10-6 M and then again in presence of a fixed concentration of L-Nitro Arginine Methyl Ester (L-NAME) 10-4 M and Nebivolol 10-6 M together in a series of experiments using six sets of isolated tracheal muscle strips in each case. Results: Nebivolol did not produce any significant shift in the concentration response curve while in the presence of L-NAME, Nebivolol shifted the histamine concentration response curve upwards and to the left. Conclusion: Nebivolol does not augment the histamine induced contraction of respiratory smooth muscle of guinea pig but in the presence of Nitric Oxide inhibitor L-NAME a significant augmentation of the same curve occurs, indicating a role of NO in the sparing of respiratory smooth muscle by Nebivolol. Keywords: Nebivolol, L-NAME, Concentration response curve, Tracheal muscle